Análise dos principais determinantes da criminalidade no Brasil: 2001 – 2005. - Bitu, Gardênia Barbosa Torres (2008)
The violence and criminality have become a constant problem for all the population. With this, literature on the economy of the crime has expanded quickly, being focused principally in the relation between the indicators of economical inequality and the distribution of the crimes between the regions. Moreover, some authors had started to study the impact of the public expenses in security and social assistance on criminality. Ahead of this scene, and being based on the economics theory of crime, this work evaluated the signal and the magnitude of the public expenses effect, beyond the socioeconomics factors, on crime in Brazilian states. Using the panel data methodology, the results gotten with fixed effect had pointed the income concentration as an important determinative factor of criminality. Regard to the public expenses effect, it was observed that the expenses with public security exert a negative effect on crime; in such way, an increase in this type of expense diminishes the criminality tax. However, the gotten results had indicated that expenses with social assistance do not exert any impact on crime, suggesting that this type of expense is not an important factor for the reduction of crime.